Quality variation of fruits of species of the genus Lycium in Ukraine: A comparative morphological analysis - Zhurba, M. Y.; Klymenko, S. V.; Szot, I. (Regulatory Mechanisms in Biosystems, 2021)
Goji berries (Lycium L.) have been an important element of traditional Chinese medicine for centuries due to their health-promoting properties and chemical composition, and they deserve the term “superfruit”. The objective of this study was to evaluate the morphological parameters of Lycium (L. barbarum L., L. chinense Mill. and L. truncatum Y. C. Wang) fruits for 21 cultivars and varieties from the collections in the M. M. Gryshko National Botanical Garden of NAS of Ukraine (Kyiv). Cultivars and varieties differed by weight, shape, and size of fruits. Their morphometric parameters were the following: fruit weight from 0.44 (L. truncatum cv. Princess Tao) to 1.08 (L. chinense cv. Tybet) g, fruit length from 10.41 (L. chinense cv. Delikat) to 22.84 (L. truncatum cv. Super Sweet) mm, fruit diameter from 7.16 (L. truncatum cv. Princess Tao) to 13.48 (L. chinense cv. Delikat) mm, number of seeds in fruit from 1.0 to 49.0. The shape indexes of fruits were found ranging from 0.78 (L. chinense cv. Delikat) to 2.56 (L. truncatum cv. New Big). The analysis of coefficient of variation showed the difference of variability in morphometric characteristics between Lycium spp. cultivars and varieties. The most variable features are fruit weight (11.4–37.1%) and number of seeds in fruits (9.7–60.8%), which are important parameters for selection that indicates about potential success of selection. Using the cluster analysis with the Bray-Curtis similarity index allowed us to establish the relationships among the fruits Lycium spp. germplasm and arrange the cultivars and varieties into three relatively main clusters. Plants of the genus Lycium, due to the growing importance as functional food, require systematic research work. In cases of food use, large fruit size is important. In the results of our research on L. barbarum, L. chinense and L. truncatum, in terms of fruit sizes the following cultivars and varieties stand out : LB02, LC Amber Sweet and LT Super Sweet. The collected varieties can be the basis for obtaining new cultivars distinguished by the size of crops and their quality.